Trpm7 Mediates Kidney Injury, Endothelial Hyperpermeability and Mortality During Endotoxemia - Cabello-Verrugio, C (Springer Nature, 2020)
Sepsis is the main cause of mortality in patients admitted to intensive care units. During sepsis, endothelial permeability is severely augmented, contributing to renal dysfunction and patient mortality. Ca2+ influx and the subsequent increase in intracellular [Ca2+]i in endothelial cells (ECs) are key steps in the establishment of endothelial hyperpermeability. Transient receptor potential melastatin 7 (TRPM7) ion channels are permeable to Ca2+ and are expressed in a broad range of cell types and tissues, including ECs and kidneys. However, the role of TRPM7 on endothelial hyperpermeability during sepsis has remained elusive. Therefore, we investigated the participation of TRPM7 in renal vascular hyperpermeability, renal dysfunction, and enhanced mortality induced by endotoxemia. Our results showed that endotoxin increases endothelial hyperpermeability and Ca2+ overload through the TLR4/NOX-2/ROS/NF-κB pathway. Moreover, endotoxin exposure was shown to downregulate the expression of VE-cadherin, compromising monolayer integrity and enhancing vascular hyperpermeability. Notably, endotoxin-induced endothelial hyperpermeability was substantially inhibited by pharmacological inhibition and specific suppression of TRPM7 expression. The endotoxin was shown to upregulate the expression of TRPM7 via the TLR4/NOX-2/ROS/NF-κB pathway and induce a TRPM7-dependent EC Ca2+ overload. Remarkably, in vivo experiments performed in endotoxemic animals showed that pharmacological inhibition and specific suppression of TRPM7 expression inhibits renal vascular hyperpermeability, prevents kidney dysfunction, and improves survival in endotoxemic animals. Therefore, our results showed that TRPM7 mediates endotoxemia-induced endothelial hyperpermeability, renal dysfunction, and enhanced mortality, revealing a novel molecular target for treating renal vascular hyperpermeability and kidney dysfunction during endotoxemia, sepsis, and other inflammatory diseases. © 2019, United States & Canadian Academy of Pathology.